173k views
4 votes
In order to solve 7x² + 5x - 3 = 0 by the quadratic formula

User DEarTh
by
5.2k points

1 Answer

5 votes

We can solve a quadratic equation of the form:


ax^2+bx+c=0

The quadratic formula:


x=(-b\pm√(b^2-4ac))/(2a)

Given the equation:


\begin{gathered} 7x^2+5x-3=0 \\ a=7,b=5,c=-3 \end{gathered}

Therefore:


\begin{gathered} x=(-5\pm√(5^2-4*7*-3))/(2*7) \\ =(-5\pm√(25-(-84)))/(14) \\ =(-5\pm√(25+84))/(14) \\ =(-5\pm√(109))/(14) \\ \text{Therefore:} \\ x=(-5+√(109))/(14)\lor x=(-5-√(109))/(14) \\ x=0.3886\lor x=-1.1029 \end{gathered}

User Turque
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.